(untitled) (Contemporary Journal of Social Science Review, 2025)
Multan, known as the "City of Saints," stands as one of the oldest continuously inhabited cities in South Asia, rich in cultural heritage, historical depth, and spiritual diversity. This interdisciplinary research article explores Multan through a comprehensive lens that encompasses its historical evolution, Sufi tradition, literary contributions, economic significance, architectural heritage, and linguistic identity. Drawing upon historical texts, archaeological evidence, and literary sources, the study traces Multan’s development from its ancient origins—possibly linked to the Indus Valley Civilization—to its status as a key political and cultural hub in Islamic and colonial South Asia. The article critically engages with the decline of traditional culture in the face of globalization and consumerism, and the resurgence of regional identity through Saraiki language and literature. By examining past and contemporary cultural trends, the study offers a nuanced understanding of Multan’s role as a civilizational center. Through thematic analysis, cultural critique, and reference to classical and modern literary voices, this paper presents Multan not merely as a geographical entity, but as a living, dynamic emblem of South Asian civilization.